PERANCANGAN SISTEM INFORMASI TRANSAKSI HARIAN PERPAJAKAN ATAS JASA DI DINAS BINA MARGA DAN PENATAAN RUANG PROVINSI JAWA BARAT - Adian Nugroho Samosir; Hani Kustyanti Kusnadi; Candra Mecca Sufyana (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The tax information system is an effort to improve tax services, by making changes to the use of information technology and information systems, one of which is Income Tax. In carrying out its activities, Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat found a process for recording tax transaction data still using an input process with Microsoft Excel. The author has found the best solution for processing daily transaction lists at the Highways and Spatial Planning Office, the solution is in the form of a web with the PHP programming language and MySQL database called E-Bimatax "Electronic Bima Taxation". The author conducted this research using a qualitative approach. It is hoped that this research will provide very important benefits for the input process to be carried out.